PRECEDENT PHENOMENA AS AN OBJECT OF PERCEPTION AND EVALUATION IN THE MECHANISMS OF THE LANGUAGE GAME - Б. Абдулхаева (Web of Journals Publishing, 2024)
This article provides detailed information on precedent phenomena in the mechanisms of the language game in modern works of art.
Keywords: precedent phenomena, language game, works of art.